A review of sexual conflict theory: the battle of the sexes - Kraus, Emily (Kansas State University, 2010)
Sexual conflict is a process that occurs when the evolutionary interests of the sexes is not aligned. The theory began with Darwin in the 1800’s. His observations of sexual dimorphism and traits which did not seem to follow the rules of natural selection led him to the theory of sexual selection. Sexual selection resolved some of the issues which were noted in the evolutionary processes he observed but not all of them. For example, it did not explain traits which increased the male optimum fitness while decreasing the female optimum fitness. It was decades before the concept of sexual conflict was formulated, and even longer before the underlying mechanisms were understood. Sexual conflict is different than sexual selection and there are ways to differentiate which of these processes have occurred in a population. The main forms of sexual conflict are intralocus and interlocus conflict. These involve the interactions between alleles in the genome of the sexes. Intralocus conflict involves conflict at a single locus in the genome while interlocus conflict involves conflict between different loci. Interlocus conflict has been more extensively studied due to its association with sexually antagonistic coevolution (SAC). SAC draws the attention of scientists due to the possibility it is related to the fundamental biological process of speciation. Sexual conflict targets certain traits at defined periods in the mating process. These periods include first, the precopulatory stage which is before the act of copulation begins. Second, there is the stage during copulation but before fertilization of the embryo. Finally, there is the postcopulatory postzygotic stage which is after copulation has ended and fertilization has occurred. Each of these points in the process of mating has traits or behaviors which sexual conflict may target. This review concludes with a proposed experiment to determine if sexual conflict is occurring in a group of four genera of mosquitoes. The experiment utilizes the attributes of sexual conflict to differentiate between other processes. A major component is the consequence of mating systems on selective processes to determine if sexual conflict is involved in the evolution of male accessory gland proteins.
Keywords: sexual conflict; gene evolution; Biology, Entomology (0353); Biology, Genetics (0369)